Communication of Nonprofit Organizations in the field of Health in Spain: approaches to an analytical framework. - Alfredo Díaz, Hernán; Cuesta Cambra, Ubaldo (Historia y Comunicación Social, 2014)
Nonprofit Organizations (NPOs) in the field of health have an increasing role. Communication is strategic for the management of these organizations, but research in this field is still insufficient. The authors developed a matrix of communication analysis with input from Perez (2008), Grunig (2011) and Villafane (2013), which was applied in a exploratory empirical study of five spanish NPOs in the field of health. The analytical framework will be applied in future research on a more representative sample.
Keywords: Management; Communication; Non Profit Organizations; Health; Strategies